Pengaruh Pemberian Respiratory Muscle Training terhadap Penurunan Dyspnea pada Pasien PPOK: Studi Literatur - Mohammad Ali; Andy MA Hariandja; Rizki Kurniawan (Jurnal Fisioterapi dan Kesehatan Indonesia, 2021)
Background: Chronic Obstructive Pulmonary Disease (COPD) is a disorder that affects the movement of air in and out of the lungs which can be characterized by coughing up phlegm, chest pain, and dyspnea (shortness of breath). One of the treatments for dyspnea in COPD is Respiration Muscle Training (RMT), which is a technique that aims to improve respiratory muscle function and help reduce dyspnea. Objective: To determine the effect of Respiratory Muscle Exercises on the reduction of dyspnea in COPD patients. Methods: Literature published in the last 10 years used by Randomized Controlled Trial and Clinical Trial studies discussing RMT with dypsnea ability outcomes. Results: There are 7 literatures eligible by measuring the Modified Medical Research Council scale, Modified Borg Scale, Profile Multidimensional Dyspnea, Basic Dyspnea Index, and Transitional Dyspnea Index. RMT can reduce dyspnea in COPD. Conclusion: RMT can be used to reduce shortness of breath in COPD patients.